2015
DOI: 10.1002/ange.201501809
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping an Enzyme Binding Pocket for Enhanced and Inverted Stereoselectivity: Use of Smallest Amino Acid Alphabets in Directed Evolution

Abstract: Directed evolution based on saturation mutagenesis at sites lining the binding pocket is ac ommonly practiced strategy for enhancing or inverting the stereoselectivity of enzymes for use in organic chemistry or biotechnology. However,a st he number of residues in ar andomization site increases to five or more,the screening effort for 95 %library coverage increases astronomically until it is no longer feasible. We propose the use of as ingle amino acid for saturation mutagenesis at superlarge randomization site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Rather than applying NNK codon degeneracy encoding all 20 canonical amino acids which would require excessive screening for 95% library coverage, single codon saturation mutagenesis (SCSM) was applied at the 7‐residue site using valine as the sole building block (in addition to the respective WT amino acids). This choice was based on the fact that essentially all of the chosen seven residues have hydrophobic sidechains (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than applying NNK codon degeneracy encoding all 20 canonical amino acids which would require excessive screening for 95% library coverage, single codon saturation mutagenesis (SCSM) was applied at the 7‐residue site using valine as the sole building block (in addition to the respective WT amino acids). This choice was based on the fact that essentially all of the chosen seven residues have hydrophobic sidechains (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…However, several mutants proved to be ( R )‐selective, the best one being WAJ‐1 (L75V‐F87V‐I263V‐A264V), which favors ( R )‐ 2a with an enantiomeric ratio of er =15:85 (step 1 in Scheme ). Had we chosen double codon saturation mutagenesis (DCSM) encoding two amino acids as building blocks in addition to WT, which has been shown to be more efficient than SCSM, the screening effort would have been difficult to handle (6561 transformants for 95% library coverage).…”
Section: Methodsmentioning
confidence: 99%
“…Randomly replacing proline with glycine can simultaneously implement mutagenesis on two or more sites, and establish a larger capacity mutation library for use in subsequent high‐throughput screening (HTS). As an alternative protein engineering strategy, directed evolution has indeed achieved numerous successes in obtaining enzymes with improved catalytic properties . However, it is often held back by the lack of a suitable HTS method .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such simple models allowed to explore the related question on how the alphabet size influences protein-protein interactions (32)(33)(34)(35). Finally, works done on realistic models, offer substantial evidence that protein design with a minimalistic alphabet is possible (36)(37)(38)(39)(40). In particular, statistical analysis of protein databases demonstrated that a considerable fraction of the information encoded in natural proteins could be packed into smaller efficient alphabets of just 5 residue types (36,38,(41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%